The Teachers’ Perceptions of Using Google Translate in the Teaching of English Pronunciation - Dwi Ayu Tiara; Rifki Irawan (FOSTER: Journal of English Language Teaching, 2024)
This study aims to investigate and describe teachers’ perceptions toward the use of Google Translate as a medium for teaching English pronunciation. This study applies a qualitative method, with data collected through observation and interviews. In getting data, the writer examined three English teachers from different schools in Yogyakarta who have used Google Translate in their classrooms. The result of this study showed that teachers have both positive and negative perspectives on using Google Translate as a medium for teaching pronunciation. The positive points of using Google Translate as a learning medium are that it is suitable and effective for helping students improve their pronunciation and ease of access and use. They believe that using Google Translate as a learning media has a good effect on students, increasing their interest in and motivation to learn pronunciation. In addition, the negative points of using Google Translate are that it depends on an internet connection, and using smartphones to access Google Translate in the classroom can be a distraction for students. Although there are some negative perceptions, it can be concluded that teachers have more positive perceptions towards using Google Translate as a learning medium to teach English pronunciation.